Cognitive Behavioral Therapy on Speaking Skill - Eef Syaifullah; Vitri Angraini Hardi (Universitas Pahlawan Tuanku Tambusai, 2021)
This experimental research was conducted at the speaking class English Study Program Pahlawan University. This research is aimed to find out the effect of Cognitive Behavioral Therapy toward the students’ speaking skill. The sample of this research is speaking class as the experiment group. Experimental class consists of 23 students. Total sampling is used in this research. The instruments in collecting the data are speaking test and documentation. The data were analyzed by using SPSS 24 program. Based on the result finding, the average score in experimental class was 67,5. Based on the data Analysis of Varianceit can be seen that the class factor shows that t is 5,366 with significant (2-tailed) of 0.000 which is smaller than 0.05. It can be concluded that there is the effect of Cognitive Behavioral Therapy toward the students’ speaking skill at the speaking class English Study Program Pahlawan University.